Cleavage of Carbon Disulfide by n‐Propyldiphenylphosphine and Nickel(II) Bromide. Issue 10 (5th February 2019) - Powers, Xian B.; Aristov, Michael M.; deGuzman, Lauren A.; Olmstead, Marilyn M.; Balch, Alan L.
Abstract: Carbon disulfide is cleaved by n ‐propyldiphenylphosphine and nickel(II) bromide in a one‐step process, to form two unprecedented complexes: orange, [Ni(S2 C2 (P n PrPh2 )2 )Br(P n PrPh2 )]Br⋅CS2 (1 ) and purple [Ni{η 2 ‐SC(P n PrPh2 )2 }Br(P n PrPh2 )]Br⋅0.5CS2 (2 ). Orange (1 ) contains a dithiolene‐related ligand that results from carbon–carbon bond formation, while purple (2 ) contains a remarkable ligand in which two n ‐propyldiphenylphosphine molecules have added to a carbon atom of a CS unit that is coordinated to nickel. Abstract : Carbon disulfide is cleaved by n ‐propyldiphenyl‐phosphine in conjunction with nickel(II) bromide in a one‐step process, to form two unprecedented complexes: orange, [Ni(S2 C2 (P n PrPh2 )2 )Br(P n PrPh2 )]Br⋅CS2 and purple [Ni{η 2 ‐SC(P n PrPh2 )2 }Br(P n PrPh2 )]Br⋅CS2 .